Current Uses of Robotic Surgery for the Treatment of Benign Adnexal Conditions - Shin, Ja H.; Schortz, Jed; Sun, Mengyang; Gutierrez, Julie (Current Women's Health Reviews, 2018)
Background: Robotic-assisted laparoscopy can be safely utilized to surgically treat multiple gynecological conditions. Few studies have evaluated its role in performing adnexal surgeries. Objective: To identify which adnexal surgeries are more commonly being performed robotically and review safety and efficacy outcomes. Method: A literature search was performed using electronic databases using keywords robotic, adnexal surgery, ovarian, tubal, endometriosis, infertility, and pediatrics. Results: A limited number of studies were identified that evaluated the role of robotic technology in adnexal surgeries such as oophorectomy or cystectomy for benign adnexal masses, removal of ovarian remnant, tubal reanastomosis, adnexal surgeries performed during pregnancy, and in the pediatric population for ovarian pathology. The results of these studies are based largely on a small number of retrospective data. These studies suggest similar perioperative complication rates for robotic surgery and conventional laparoscopy for the treatment of these conditions. Conclusion: Robotic assisted laparoscopy has been demonstrated to treat adnexal pathology with favorable outcomes. However, the benefit of this technology compared to conventional laparoscopy for these procedures is undetermined and larger prospective studies are necessary to better understand its advantages and disadvantages.
Keywords: ovarian remnant